2019
DOI: 10.1186/s12894-019-0550-9
|View full text |Cite
|
Sign up to set email alerts
|

Retzius-sparing robot-assisted laparoscopic radical prostatectomy: functional and early oncologic results in aggressive and locally advanced prostate cancer

Abstract: BackgroundRetzius-sparing robot-assisted laparoscopic radical prostatectomy (rsRARP) allows entire prostatectomy procedure via the pouch of Douglas. In low- and intermediate-risk prostate cancer (PCa) there is level 1 evidence that the Retzius-sparing approach impacts early continence recovery. Since specific data on aggressive and locally advanced cancer is lacking and avoiding rsRARP is presently suggested, we investigated urinary and sexual recovery, perioperative complications and early oncologic outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 33 publications
2
19
2
Order By: Relevance
“…Similarly the distribution of biopsy GS was variable. A score below 8 in more than half of the cases was reported by few authors [11,14,16,18,19]; while a score of 8 or more was noted by others, including us [5,10,17]. However, patient's clinical stage in our study was similar to the other reports.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similarly the distribution of biopsy GS was variable. A score below 8 in more than half of the cases was reported by few authors [11,14,16,18,19]; while a score of 8 or more was noted by others, including us [5,10,17]. However, patient's clinical stage in our study was similar to the other reports.…”
Section: Discussionsupporting
confidence: 84%
“…PSA distribution among the various other studies of HRPC treatment by RP was not uniform ( Table 5). Mean PSA around 10ng/ml was found in a few studies [7,10,14,15,16,17] while a value between 15-25ng/ml was observed in others, including in our study [5,11,18,19]. Similarly the distribution of biopsy GS was variable.…”
Section: Discussioncontrasting
confidence: 44%
“…Since almost all studies focused on low-and intermediaterisk PCa, there is a gap in reporting the RS approach for the high-risk and locally advanced disease. Nyarangi, et al published the results of a cohort of 50 men with high-risk PCa treated with RS-RARP, after 1 year of follow-up, and found that this approach is feasible, oncologically safe, associated with few perioperative complications and offers good results regarding recovery of urinary continence but long term oncological outcomes are awaited and the irst results from erectile function need to be con irmed [46].…”
Section: Best Literature Datamentioning
confidence: 99%
“…As a new technical alternative, long-term oncological outcomes remain unclear and the surgeon must pay attention to own surgical margins and compare with videotapes to improve personal results. In experienced hands since high risk cases can be performed with acceptable results [52].…”
Section: Other Caractheristics Of Rs-rarpmentioning
confidence: 99%
“… 2 Among Retzius sparing radical prostatectomy (RS-RARP), lymphoceles have been reported in 10% of PLNDs for intermediate and high-risk prostate cancer. 3 We present a unique case of submassive pulmonary embolisms (PE) potentially caused by iliac compression by a large complex space of Retzius lymphocele after a RS-RARP.…”
Section: Introductionmentioning
confidence: 99%